DMPA-SC stock: Cross-site trends by facility type - Sophia Magalona; Shannon N. Wood; Frederick Makumbi; Funmilola M. OlaOlorun; Elizabeth Omoluabi; Akilimali Z. Pierre; Georges Guiella; Jane Cover; Philip Anglewicz (Elsevier, 2022)
Objectives: To measure trends in the supply of DMPA-SC in public and private health facilities and compare with other prominent modern methods. Study design: We used repeated cross-sectional data from service-delivery-point surveys in six settings: Burkina Faso, Democratic Republic of Congo (Kinshasa and Kongo Central), Nigeria (Kano and Lagos), and Uganda, each with 3-5 rounds of data collected between 2016 and 2020. We analyzed trends in DMPA-SC availability using percent of service delivery points offering the method and percent experiencing stockouts; trends were compared with those for DMPA-IM, IUD, implants, and other short-acting methods, by facility type. Results: All settings showed increased offering of DMPA-SC over time for both private and public facilities. Larger proportions of public facilities provided DMPA-SC compared to private facilities (66%-97% vs 16%-50% by 2019-2020). DMPA-SC was provided by fewer facilities than DMPA-IM (90%-100% public, 34%-69% private by 2019-2020), but comparable to implants (83%-100% public, 15%-52% private by 2019-2020) and IUDs (55%-91% public, 0%-44% private by 2019-2020). Trends of DMPA-SC stock varied by setting, with more consistent stock available in private facilities in the DRC and in public facilities in Burkina Faso and Nigeria. Uganda showed decreasing stock in public facilities but increasing stock in private facilities. Conclusion: DMPA-SC availability has been increasing since its introduction in sub-Saharan Africa, yet significant gaps in stock exist. Countries should consider alternative distribution models to address these issues. Implications: Our findings may help inform countries about the need to monitor DMPA-SC availability and to consider solutions that ensure contraceptive options are available to women who need them and disruptions to contraceptive use are minimized.